Conversational Implicature in Tawfiq Ahmad's Poetry The poem "Damascus Alsham" as a model: conversational implicature (Journal of Hama University, 2026)
The research studies the phenomenon of conversational implicature in Tawfiq Ahmad’s poetry. It studies the definition of conversational implicature and its types, studies co-operative principle  and the conversational rules related to, and differentiates between the characteristics of conventional implicature and conversational implicature. It analyzes the phenomenon of conversational implicature in the poem "Damascus alsham" by the poet "Tawfiq Ahmed" by studying how the transformation from direct explicit meanings to indirect implicit implied meanings that the rhetorical images, declarative and constructive styles indicate it, and the pragmatic purposes that result from them in the light of the context of the production of the discourse and its situation, and the effect of that on understanding the poet's intentions and interpreting the poetic discourse.
Keywords: conversational implicature, conventional implicature, co-operative principle , conversational rules, explicit meanings, implicit meanings.